A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
anonymous
 4 years ago
Explain why (–4x)0 = 1, but –4x0 = –4.
anonymous
 4 years ago
Explain why (–4x)0 = 1, but –4x0 = –4.

This Question is Closed

agreene
 4 years ago
Best ResponseYou've already chosen the best response.2I assume you're asking why: \[(4x)^0=1\] whilst \[4x^0=4\] and the answer is that anything to the 0 is defined as 1. and the order of operations: (4x)^0 is saying the variable and coefficient are to the 0 while 4x^0 is only taking the variable to the 0 which means: \[4x^0\implies4(1)=4\]

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0what agreen said. for the same reason that \[2\times 3^2=2\times 9=18\] but \[(2\times 3)^2=6^2=36\]
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.